Dadas as funções F (x) = x2-5 e g (x) = 3x -1 determine F (g(-1) ) e g (F ( (- 2) )
Soluções para a tarefa
Respondido por
1
I - f(g(-1))
g(-1) = 2.(-1) - 5 f(-7) = 3.(-7) - 1
g(-1) = - 2 - 5 f(-7) = - 21 - 1
g(-1) = - 7 f(-7) = - 22
II - g(f(-2))
f(-2) = 3.(-2) - 1 g(-7) = 2.(-7) - 5
f(-2) = - 6 - 1 g(-7) = - 14 - 5
f(-2) = - 7 g(-7) = - 19
g(-1) = 2.(-1) - 5 f(-7) = 3.(-7) - 1
g(-1) = - 2 - 5 f(-7) = - 21 - 1
g(-1) = - 7 f(-7) = - 22
II - g(f(-2))
f(-2) = 3.(-2) - 1 g(-7) = 2.(-7) - 5
f(-2) = - 6 - 1 g(-7) = - 14 - 5
f(-2) = - 7 g(-7) = - 19
DanielOliveira14:
acho que é assim que se resolve. Se eu errei me desculpe.
Perguntas interessantes
Matemática,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás